Effect of COVID 19 on thyroid gland function - Mohammed, Hussein Adnan; Omairi, Saleh Salman (Journal of Drug Delivery and Therapeutics, 2021)
The pandemic caused by the new Coronavirus (SARS-CoV-2) and the disease induced by it (Coronavirus Disease or COVID-19) has been filling the pages of newspapers, television news and websites for days. It is a new virus, which until a few months ago probably lived only in bats, about which there is little scientific certainty about humans. The few evidences, however, are constantly updated and evolving. It is therefore not uncommon to come across information from unreliable sources and / or without any scientific basis. As far as possible, I will try to shed some light on the possible relationships between the new SARS-CoV-2 coronavirus and the endocrinological system. This article, therefore, is the result of a completely personal research carried out in scientific journals, international scientific research sites and on the opinion of experts in the sector (expert opinions). It does not presume to be exhaustive, as the current certainties are very few and in any case must be interpreted dynamically since the scientific framework is constantly evolving. In essence, the information reported at the time of writing this article is based on what is currently known about the COVID-19 infection, but could be outdated in the coming months, based on the finding of new scientific evidence.Keywords: Effect, COVID 19, thyroid, gland, function